2021
DOI: 10.1210/clinem/dgab447
|View full text |Cite
|
Sign up to set email alerts
|

Brown Adipose Tissue, Adiposity, and Metabolic Profile in Preschool Children

Abstract: Context An inverse relationship between brown adipose tissue (BAT) and obesity has previously been reported in older children and adults, but unknown in young children. Objective We investigated the influence of BAT in thermoneutral condition on adiposity and metabolic profile in Asian preschool children. Design, Setting and Participants A total of 198 childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…With an increase in age, BAT in rodents showed volume atrophy and mitochondrial function decline. Studies have shown that activated BAT is associated with lower body mass index in preschool children [ 26 ], but no sufficient evidence has demonstrated the relationship between BAT and total fat mass in the elderly. Our study found that BAT mass is unconcerned with total fat mass in elderly SAMP8 mice.…”
Section: Discussionmentioning
confidence: 99%
“…With an increase in age, BAT in rodents showed volume atrophy and mitochondrial function decline. Studies have shown that activated BAT is associated with lower body mass index in preschool children [ 26 ], but no sufficient evidence has demonstrated the relationship between BAT and total fat mass in the elderly. Our study found that BAT mass is unconcerned with total fat mass in elderly SAMP8 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue composition and localization also differs by sex, and even in utero and at birth greater total fat mass in females is already apparent. Furthermore, females typically have a higher proportion of brown adipose tissue than males ( 34 ). These fundamental biological sex differences may contribute to the different mother-offspring relationships observed in sons and daughters if adipose tissue morphology and biology in males and females are differentially programmed by early life exposures, as has been suggested in some animal studies ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that higher BAT mass in individuals is associated with cardiometabolic health [880][881][882][883].…”
Section: Thermogenesis and Batmentioning
confidence: 99%